SOD PRODUCTION AND NUTRIENT EXTRACTION BY EMERALD ZOYSIAGRASS WITH SPLIT NITROGEN APPLICATIONS - Godoy, Leandro José Grava de; Villas Bôas, Roberto Lyra; Backes, Clarice; Soares, Edhielle Vanessa de Lima; Santos, Alessandro José Marques; Lima, Claudinei Paulo de; Fernandes, Dirceu Maximino (Scientia Agraria, 2017)
Nitrogen is the nutrient that provides the best grass growth responses, and proper nitrogen fertilization can enable the formation of sod in less time and firm enough to be handled after harvest. The aim of this study was to evaluate production and nutrient extraction of Emerald zoysiagrass (Zoysia japônica Steud.) according to the splitting of nitrogen doses. Treatments consisted of five doses (0, 150, 300, 450 and 600 kg ha-1) divided in to four applications, provided the formation of Emerald zoysiagrass sods six months after the previous sod harvest. Nutrient extraction by Emerald zoysiagrass occurs in the descending order, em kg ha-1: N (207) > K (57) > (Ca) > S (27) > P (14) = Mg (14).